Influence of different organomodified clays on the viscoelastic response of ethylene vinyl acetate//poly(vinyl chloride)/organoclay nanocomposites. (November 2015) - Gehlen, Aline; Ornaghi Junior, Heitor Luiz; Pistor, Vinicius; Covas, José António; Zeni, Mara; Zattera, Ademir José
Nanocomposites were prepared by melt mixing in a twin-screw extruder 5% by weight of Cloisite ® Na +, 15A or 30B, with an ethylene vinyl acetate/poly(vinyl chloride) (EVA/PVC) blend (90/10% by weight). The dispersion was assessed by X-ray diffraction (XRD), transmission electron microscopy (TEM), oscillatory rheometry, and dynamic mechanical analysis (DMA). XRD and TEM analyses revealed an intercalated morphology and an exfoliated morphology for the composites containing Cloisite 15A and 30B, respectively. Rheometrical and DMA data demonstrated that the presence of PVC in the blend not only improved the interaction with Cloisite 30B but also acted as a mechanical reinforcement.